DAMPAK PENGGUNAAN GAME ONLINE TERHADAP KEMAMPUAN BERKOMUNIKASI ANAK - Lusi Asmiati; Ika Ari Pratiwi; Much Aryad Fardhani (IKIP Siliwangi Bandung, 2021)
All students admitted that they had been given cellphones by their parents, and all of them had online game applications. This study aims to explain the impact of using online games on children's communication skills. This research is a descriptive study with a qualitative approach. This research is located in the village of Pagendisan Dukuh, Kampung Metu Pati, Central Java, with the subjects of grade IV elementary school students. Data collection techniques in this study were interviews, questionnaires, observation, and documentation. Data analysis in the study consisted of data collection, data reduction, data display, and verification. Child A starts addicted to online games and has an impact on verbal and nonverbal communication skills in the less category. Child B is an online game addict and has an impact on verbal and non-verbal communication skills in the poor category. Children C are not addicted to online games, even for children C online games have a positive impact, such as getting English words and drawing clothes designs. Child D becomes addicted to playing online games. His addiction to playing online games affects children's communication skills. D. In conclusion, the impact of using online games on children's communication skills depends on the child's category in the intensity of time playing online games